THE PHILOSOPHY OF CONTEMPORARY EDUCATION AND ITS IMPLICATIONS FOR THE DEVELOPMENT OF ISLAMIC EDUCATION - Lukman S Thahir (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2022)
The title of this research is Theoretical Debate over the Philosophical Roots of Contemporary Education and Its Implications for the Development of Islamic Education. The purpose is to disentangle, to explore and to discuss the foundations of theoretical roots of educational philosophy and its relational consequences with Islamic education. The issues raised are: 1). how is the philosophical foundation of education and its relationship to philosophy and education? 2). what are the Philosophical Roots of Educational Theory and Its Implications for Curriculum, Teaching and Learning? 3). what are the implications for the development of Islamic education? The type of research is Library Research which uses philosophical and pedagogical approach, with descriptive method. The findings of this study are: a) the study of the key philosophical ideas that influence thought and development of education are aspects of metaphysics, epistemology and axiology. Without these three philosophical foundations, science and its various disciplines will fail; b) the relationship between philosophy and education are like two sides of one coin that cannot be separated, both give and take in the context of mutualism. So the existence of philosophy in education is a necessity; c) The theoretical debate over the roots of the philosophy of education requires the development of Islamic education.